A Constraint-Driven Generative Design Methodology for Modular Actuated Robotic Components in Decentralized Manufacturing - Pedro Portugal (International Journal of Robotics and Automation in Mechanics, 2026)
This work formalizes a constraint-driven generative design framework for actuator-integrated robotic components intended for decentralized additive manufacturing. Conventional topology optimization typically prioritizes structural efficiency while treating actuator integration, modular interfaces, and fabrication constraints as secondary considerations. In contrast, the proposed methodology encodes these requirements as first-order geometric and mechanical constraints prior to automated material redistribution. The framework defines preserved actuator geometry, bounded design envelopes, representative loading abstractions, and manufacturability-aware domains to guide structural synthesis within physically admissible regions. A mathematical formulation expresses the design task as a constrained mass minimization problem subject to equilibrium, stress, geometric preservation, and manufacturability conditions. By embedding engineering intent directly into the generative problem definition, the methodology ensures that synthesized geometries remain mechanically plausible, assembly-compatible, and fabrication-ready without post hoc correction. This constraint-driven approach reduces design iteration overhead, improves reproducibility, and aligns generative outputs with the realities of consumer-grade additive manufacturing. Although motivated by actuator-integrated robotic links, the framework is architecture-agnostic and generalizable to a broad class of modular robotic components fabricated under distributed and resource-limited production environments. The approach provides a reproducible foundation for engineering-aware generative synthesis in decentralized robotic hardware development and supports scalable, accessible mechanical innovation across diverse applications and contexts globally.
Keywords: Additive manufacturing; Modular robotics; actuated robotic components; constraint-driven design; decentralized manufacturing; generative de-sign tools